An overview of upland rice research : (International rice research institute, 1984)
The proceedings consist of papers presented on the workshop held at Bouake, Ivory Coast, in 1982. It contains base line papers on upland rice production for Africa, Asia, India, and Latin America and papers on: (1) environmental characterization and classification (2) plant protection; (3) soil and crop management; (4) varietal improvement and 5 cropping systems. The information presented in this volume can serve as a background on which to base future upland rice research and development programmes